Alternative treatments for footwear industry liquid effluents - Part 3 - Pressure wet hydrogen peroxide oxidation - M. J. Ferreira (2002)
Footwear industry finishing operations generate non-biodegradable liquid effluents having a high organic load, mainly due to dyes, organic acids and organic solvents. Coagulation/flocculation followed by carbon adsorption is one option for treating these effluents, since it may allow the discharge of the final effluent to sewage systems but not to water courses. The process is of dubious utility due to the sludge produced and the required adsorbent amount. Such limitations pushed the research towards wet oxidation (WO) already tested with oxygen as oxidant.(1) The reduction of effluent chemical oxygen demand (COD) with this treatment at 200degreesC ranges from 50 - 80%, depending on the conditions and the initial COD of the wastewaters. However, residual COD values are too high for discharging the effluent to public sewage systems. Therefore, WO using hydrogen peroxide is the alternative method tested here. The experiments carried out evaluated the influence of temperature, time, H2O2 dose and pH on the reduction of effluent chemical oxygen demand (COD) and other characteristics of the wastewaters. The catalytic effect of iron on the WO treatment efficiency was also evaluated.